2005
DOI: 10.2320/matertrans.46.2268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg Content on Vibration Fracture Resistance of Friction Stirred Al–Mg Alloys

Abstract: In this study, the effect of Mg content on friction stirred Al-Mg alloy is discussed, and the experimental results indicate that grains of parent plate which are refined through FSP (friction stir processing) are effective in enhancing tensile properties of materials through FSP and improving the vibration fracture resistance of friction stirred specimens. It should be noted that the deterioration of vibration fracture resistance can be recognized as Mg content increases, the grain size actually has been refin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The friction stir process (FSP) [1][2][3][4] is an innovative process that developed from friction stir welding (FSW) [5,6]. FSP was adopted in this study because its friction rotation between the tool and specimen can produce a plastic deformation flow to obtain finer recrystallized grains and improve the material characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The friction stir process (FSP) [1][2][3][4] is an innovative process that developed from friction stir welding (FSW) [5,6]. FSP was adopted in this study because its friction rotation between the tool and specimen can produce a plastic deformation flow to obtain finer recrystallized grains and improve the material characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The D-N curves also show a distinct plateau stage of maximum deflection in-between the initial ascending stage and the final descending stage, except for H112 and FS specimens. Based on our previous investigation [9], the deflection amplitude dropping from its peak indicates a deviation of the actual vibration frequency from the resonant frequency. Therefore, the vibration life in this study as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The 5052 alloys processed by hot rolling (H112) and subsequent friction stirring using a best set of fixed FS parameters were compared with those processed by cold rolling with various rolling reductions. Based on previous experimental results [9,10], the vibration fracture resistance depends on vibration test conditions and material characteristics, respectively. The major difference between hotrolled and cold-rolled specimens is the microstructural feature, which depends mainly on the imposed prior strain.…”
Section: Introductionmentioning
confidence: 99%